Changing policy paradigms: How are the climate change mitigation-oriented policies evolving in Nepal and Bangladesh?. Issue 124 (October 2021) - Baniya, Bishal; Giurco, Damien; Kelly, Scott
Highlights: Climate mitigation actions are getting attention in the policy discourse in both Nepal and Bangladesh. Content analysis of government policies shows changes in policy paradigms from adaptation to mitigation. Delivery of climate mitigation actions remains weak despite a notable paradigmatic change in policies. Abstract: The inclusion of climate mitigation actions in the Nationally Determined Contributions and climate policies of low-income countries such as Nepal and Bangladesh means that policymakers are seeking to address both types of responses to climate change. This study assesses changes in policy paradigms pertinent to climate mitigation, in Nepal and Bangladesh for the period from 1992 to 2018. Policy paradigm refers to the framework of policymakers' ideas and strategies that influence the formulation of policies across different aspects. This research develops and uses an analytical framework which considers the following aspects of public policy: (i) problems and focus; (ii) content (policy instruments and financial resources); (iii) institutions and strategic interactions; and (iv) global environment-related initiatives. Relevant policies (18 for Bangladesh and 17 for Nepal) were analyzed and thematically coded using NVivo software. While most aspects showed notable change over time, the institutions and strategic interactions aspect showed only incremental change. Although primarily focussed on adaptation, a new policy paradigm that seems to have emerged post-2005 for Nepal and Bangladesh focuses on low carbon development, access to energy, sustainable transport, and sustainable agricultural practices. To operationalize the new policy paradigms in both countries, economic and market-based policy instruments that utilize the government's internal funding will need to support policies to minimize the impacts of changes in official development assistance.